'Foldscope'- A simple and economical microscope. Issue 2 (15th March 2021) - Das, Karabi; Dutta, Papia; Gogoi, Jyotchna
ABSTRACT: A Foldscope is an ultra-affordable paper microscope with a magnification up to 2000X and 2 micron resolution. It is economic, durable and easy to handle tool for scientific studies. Many govt. schools of Kamrup district, Assam found it difficult to use microscope in their regular practical classes for its complexity and high cost. For visualization of specimen under Foldscope, light source used is either natural light (during day time) or artificial light source operating on batteries. Being extremely light weight and portable, it could be easily carried along to field for various studies. In the present study, practical sessions and awareness on this instrument was conducted in the govt. and private schools of Kamrup (M), Assam. Students and school authority's feedback were collected for analyzing the scope of Foldscope in future use as a part of their syllabus. The hands on training of the instrument helped the student's to understand microscopic world of biology. Hence, it could be concluded that Foldscope could be incorporated in every school's syllabus for better understanding of biology by reducing school experimental expenses and overcoming the facility constraints.